Factors Affecting Work-Study-Life Balance among MBA Job Holder Students at Pokhara University (Journal of Development and Social Engineering, 2024)
The increasing role of students as both earners and learners has heightened the significance of achieving Work-Study-Life Balance (WSLB), particularly in Nepal, where the rising cost of education, limited skills, and time constraints pose unique challenges. This study investigates the factors influencing WSLB among MBA jobholder students at Pokhara University. Following a quantitative approach, this study employed descriptive as well as causal comparative research design. Data were collected from 125 respondents purposively through a structured questionnaire. The analysis utilized descriptive statistics to measure the perception of students towards WSLB and Partial Least Squares-Structural Equation Modeling (PLS-SEM) to examine relationships among the four independent variables—organizational support, family support, academic life, and personal life at work—and the dependent variable, WSLB. Mean score analysis indicates positive perceptions of organizational support, family support, manageable academic life, and personal effectiveness among the students. Further, the study found organizational support and personal life at work significantly and positively affect WSLB. The study underscores the importance of fostering supportive organizational cultures, offering flexible academic programs, and encouraging family involvement to enhance WSLB. This research contributes to the limited literature on WSLB in Nepal, offering actionable insights for organizations, educational institutions, and families to create environments that support students’ academic, work, and personal success.